USING WORD SQUARE GAME TO TEACH VOCABULARY TO THE SECOND GRADERS OF SMP NEGERI 2 PAKEL - Pujiastuti, Diah Arum (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
One of the games used in teaching vocabulary is word square game. Word square game is one of games which is used to the teacher in learning goal. Word square game is a set of words arranged so it can be read left to right, right to left, top to bottom, and bottom to up. It is used to be easier the students absorb materials in their learning process and it is a one of review and assesses new vocabulary. It will help teacher easier to teach vocabulary and it will help the students get new word easier to mastery vocabulary. The research design was pre experimental design with one group pretest and posttest with quantitative approach. The population of this research was all students of second grade at SMP Negeri 2 PAKEL. The sample was VIIIC class consisting of 26 students through random sampling. The research instrument was test. The data analysis was T-test. The research finding in this research showed that the difference between the averages of students? vocabulary score before they are taught using word square game was 56.69. While the students? vocabularies score after they are taught using word square game was 73.46. Statistical calculation using T-test showed that significance value < 0.05. The Tcount was -12.637. This means that Ho which states that there is no significant effect in using word square game to teach vocabulary to the VIIIC grade at SMP Negeri 2 PAKEL is rejected. In other words, word square game can be used as an alternative to teach vocabulary to the students at Junior High School level.